Innovation and entrepreneurship in Latin America: What do we know? What would we like to know? - Álvarez, Roberto; Grazzi, Matteo (Estudios de Economía, 2018)
The long-run economic performance of Latin America has been unsatisfactory especially in comparison with other emerging economies, which have been able to “catch up” with developed countries. The historically low innovation and dynamic entrepreneurship rates have been identified as two of the main reasons for this situation. In this paper, we present a synthetic but comprehensive review of the empirical literature related to these topics in the region, as well as the results of the main impact evaluations performed to assess innovation and entrepreneurship policies implemented in Latin America. This review, together with the identification of unexplored or underexplored areas of research, is functional to introducing the investigations that are part of this special issue.